Assay of Steroidal Sapogenin in Costus Speciosus Rhizomes - JAHFAR, M.; ABDUL RAHIM, A.K.; JINCY, A.; UNNIKRISHNAN, K.P. (Asian Journal of Chemistry, 2010)
Diosgenin, a steroidal sapogenin, was isolated from rhizhomes of Costus speciosus by reported method. It was characterized by TLC, UV and FT IR spectroscopy and purity was determined by HPLC. Amount of diosgenin in the free and glycosidic form was determined colorimetrically, after subjecting the purified sample to preparative TLC. Result shows that the majority of diosgenin is in the glycosidic form.